National Health Insurance Scheme and Child Healthcare Delivery in the Ga East District - Asah, A. (University of Ghana, 2013)
The increasing cost of healthcare delivery has become a major issue in developed and developing countries. Resultantly, health policy makers are faced with competing alternatives for the systems of healthcare financing. Health Insurance schemes are thus seen as viable alternatives to providing a more sustainable and equitable health delivery system in countries. This study examined the role of the National Health Insurance Scheme in effective child health care delivery in the Ga East District of Ghana. The study adopted quantitative and qualitative techniques through structured questionnaires and in-depth interviews for respondents who had insured their children and those who had not in four (two urban and two rural) selected communities in the Ga East District. A total of 300 structured questionnaires were administered to respondents. Kendall‟s coefficient of concordance, binary logit model, chi square and t test were used to analyse the data. Findings from the study showed that socio-economic factors and distance from respondents‟ residence to accredited NHIS health facilities significantly influence child enrolment and utilisation of the scheme. Further, there was a significant difference in the perceptions of parents of insured and uninsured children of the quality of healthcare they received. Lastly, challenges respondents encountered in accessing the scheme and subsequently accessing healthcare for their children under the scheme also influenced child enrolment on the scheme negatively. Therefore, the study recommends among other things that the NHIA should intensify their regular monitoring accredited health centers to assess services under the scheme to ensure an optimal operation of the scheme. In this regard, regular workshops should be organized for hospital information officers to update them on any changes in the scheme.
Thesis (MPHIL)-University of Ghana, 2013